1995
DOI: 10.1144/sjg31020171
|View full text |Cite
|
Sign up to set email alerts
|

The first Middle Jurassic dinosaur from Scotland: a cetiosaurid? (Sauropoda) from the Bathonian of the Isle of Skye

Abstract: Synopsis The limb bone of a dinosaur was discovered from the Valtos Sandstone Formation (Bathonian, Middle Jurassic) near Valtos, Isle of Skye. The bone preserves the eroded proximal and distal ends and is missing the mid-shaft. It represents the first unequivocal Middle Jurassic dinosaur bone from Scotland. The bone is of a sauropod dinosaur and may be the femur of a cetiosaurid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…If the trackmaker genus in Wyoming is the same as the trackmaker for the similar footprints in Scotland, then its presence at these two distant locations needs to be explained. One hypothesis is that they may have migrated between these two locations following sauropods which certainly existed in Scotland at this time (Clark et al 1995;Barrett 2006;Liston 2004). It has been suggested that some Cretaceous hadrosaur dinosaurs migrated, but this has been disputed (Fiorillo & Gangloff 2001;Lockley 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the trackmaker genus in Wyoming is the same as the trackmaker for the similar footprints in Scotland, then its presence at these two distant locations needs to be explained. One hypothesis is that they may have migrated between these two locations following sauropods which certainly existed in Scotland at this time (Clark et al 1995;Barrett 2006;Liston 2004). It has been suggested that some Cretaceous hadrosaur dinosaurs migrated, but this has been disputed (Fiorillo & Gangloff 2001;Lockley 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A theropod tibia was found in the Broadford Beds Formation (Hettangian) in the Strathaird Peninsula, southern Isle of Skye (Benton et al 1995), a thyreophoran ulna and radius came from the Bearreraig Sandstone Formation (Bajocian) at Bearreraig Bay, northern Isle of Skye (Clark 2001b), and cetiosaur bones and a coelophysoidgrade tail bone were discovered in the Valtos Sandstone Formation (Bathonian) at Dun Dearg near Staffin (Clark et al 1995Liston 2004). The latest discovery has been of a sauropod tooth from the Kilmaluag Formation (Bathonian) near Glen Scaladal, north of Elgol, Isle of Skye (Barrett 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Scotland boasts one of the world's premier Middle Jurassic small vertebrate faunas (Evans & Milner 1994;Evans et al 2006), which includes spectacularly well-preserved specimens of one of the oldest turtles (Anquetin et al 2009) and some of the closest relatives of mammals (Waldman & Savage 1972). Tantalizing bones and footprints of dinosaurs have been found in several Early-Middle Jurassic units, making Scotland one of the rare places in the world to yield dinosaurs from this under-sampled time interval (Andrews & Hudson 1984;Clark et al 1995Clark et al , 2004Clark et al , 2005Clark & Rodríguez 1998;Clark 2001;Liston 2004;Marshall 2005;Barrett 2006). Most of these new discoveries have come to light over the past 25 years and, during this time, Scotland has emerged as a growing, but still underappreciated, centre of Mesozoic vertebrate palaeontology research.…”
Section: Introductionmentioning
confidence: 99%
“…Dinosaurs, stem mammals, turtles, squamates and lissamphibians from Skye have been the focus of most recent work on the Hebridean vertebrates, and have been well described and figured in the literature (e.g. Waldman & Savage 1972;Waldman & Evans 1994;Clark et al 1995;Anquetin et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A theropod tibia was found in the Broadford Beds Formation (Hettangian) in the Strathaird Peninsula, southern Isle of Skye (Benton et al, 1995), a thyreophoran ulna and radius came from the Bearreraig Sandstone Formation (Bajocian) at Bearreraig Bay, northern Isle of Skye (Clark, 2001b), and cetiosaur bones and a coelophysid-like tail bone were discovered in the Valtos Sandstone Formation at Dun Dearg near Staffin (Clark et al, 1995;Clark et al, 2004).…”
Section: Introductionmentioning
confidence: 99%